PERBANDINGAN ANTARA PEMBERIAN ASAM FOLAT, EKSTRAK GINKGO BILOBA, DAN METHYL COBALAMIN TERHADAP INDEKS APOPTOSIS DAN EKSPRESI CASPASE 3 PADA INTOKSIKASI METANOL SEL GANGLION RETINA - Prayitnaningsih, Seskoati; Sumarno, Sumarno (Jurnal Kedokteran Brawijaya, 2005)
ABSTRACT Permanent  visual  damage  caused  by  methanol  intoxication  has  been  associated  with  prolonged  exposures  to  blood formate  concentrations.  Formate  accumulation  disrupt  mitochondrial  energy  production,  which  subsequently  lead  to caspase 9, 3 activation and finally causes apoptosis.  Folic acid (FA) has been used as adjunctive therapy to enhance the rate  of  formate  metabolism.  Extract  Ginkgo  biloba  (EGb)  the  most  popular  herbal  therapy  possess  is  antioxidant  and antiapoptotic capacity. On the other hand, Methyl cobalamin, a kind of endogenous co enzyme B 12 can promote nucleic acid and protein synthesis. To compare the effect of FA, (EGb), and Methyl Cobalamin (MC) to Apoptotic Index (AI) and Caspase 3 expression of  retinal ganglion cell induced by methanol intoxication (MI). Experimental study was conducted in Pharmacology and Biomedic laboratory of Brawijaya University for two weeks. Fifteen rats were included, and divided into five groups: (a) control, (b) Methanol Intoxication only, (c) Folic Acid 1 mg day per os, (d) Extract Ginkgo biloba 50 mg/kb  per  os,  and  (e)  Methyl  Cobalamin  500  microgram/kg  intraperitoneally  for  three  days.  MI  were  done  by  giving methanol 4 g/kg in the first day, and 2 g/kg for two days after. Apoptotic Index and Caspase 3 expression were assessed